0=5u+3

Simple and best practice solution for 0=5u+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=5u+3 equation:


Simplifying
0 = 5u + 3

Reorder the terms:
0 = 3 + 5u

Solving
0 = 3 + 5u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-5u' to each side of the equation.
0 + -5u = 3 + 5u + -5u
Remove the zero:
-5u = 3 + 5u + -5u

Combine like terms: 5u + -5u = 0
-5u = 3 + 0
-5u = 3

Divide each side by '-5'.
u = -0.6

Simplifying
u = -0.6

See similar equations:

| -37-3x=12-10x | | 111-4x=3x+6 | | 16=2(2w+w-1) | | 65-4x=8x+17 | | 3-3(x-2)= | | 7x-2=10x+10 | | 6x^3+14x^2+(12xy^2)= | | 5(x-4)+x=6(x-4)+4 | | 6(10x-4)=-8 | | 0=-4v-7 | | 105-5x+9x=21 | | x+6=(7-x)+5 | | 4(11x+6)=-9 | | 3x+6=87-6x | | 6x^3+14x^2+12xy^2= | | 11x^2+180=1024 | | 3(5x+2)-7x=38 | | 236-7x=29x+24 | | 11n=9n | | -8w+14=14 | | 5x^3+7x^2+2x= | | k^2+2k-15=0 | | 3x-3=10x-52 | | 5x^2-8x+2=0 | | 12+2(x-4)+3x=74-5x | | 2x+32=12x-58 | | 8x+2=8x+2 | | 155-6x=6x+23 | | 6x+39=9x+12 | | 9x+6=6x+15 | | 3(x+2)=2x+1+9 | | 5x+5=104-6x |

Equations solver categories